Valuable Subversions: Gendered Generativity and Sorcerous Production in Central Mozambique - Bjørn Enge Bertelsen (Valuation Studies, 2016)
How is one to analyze the existence of a subterranean dwarfish couple (zwidoma) occupying the space underneath cooking places and whose central purpose is to reinforce a market woman’s sales—but simultaneously feeding off her very body? Using urban and rural ethnographic material from central Mozambique, where such assemblages comprising the zwidoma and a woman are integral to economic life and social orders, this article contextualizes such constellations—effectively interferences within various domains of value—by undertaking an analysis of gendered modalities of generativity. Further, by meditating on various understandings of cosmology and, ultimately, the dynamics constituting the realms of the real, it presents an alternative to influential analyses of capitalism, such as the notion of “occult economies.” An argument is made not only for value’s dynamic and changeable nature but also for the necessity to appreciate instances of its subversion with destructive effects. The article underlines, therefore, how such subversions of value, in various forms, is in line with Tsing’s (2015) general argument that critical explorations of capitalism and regimes of valuation and production are best undertaken in peri-capitalist zones—such as urban and rural Mozambique.